Mixed-Initiative tool to speed Up content creation in physics-based games - Gennaro Campos, Cesar Ruben Francisco (2017)
In this work we introduce a mixed-initiative tool to speed up the process of con- tent generation for physics-based games. Our system uses exhaustive search and computational geometry to allow the game designer to focus on the creative process of content creation by not needing to worry about the manual construction of the game structures. We use a clone of Angry Birds called Science Birds as testbed for our research. A user study shows the advantages of employing our mixed-initiative tool for creating Angry Birds levels. Namely, our study showed that people are able to create Angry Birds levels much more quickly using our mixed-initiative tool than a baseline system. Moreover, the levels created with our mixed-initiative tool are comparable in terms of quality with those created with the baseline system. Finally, the participants of our study reported to be easy to use our tool and that they were more satisfied with their experience than the participants who used the baseline.